Cross-Section Resistivity Detection of Tree (Swietenia Magahoni and Gmelina) Using ERT Method - Evi Fazriati; Asep Purnama; Gian Agistian Algifari; Irene Siti Amilah Muslimah; Fitria Hapsari Puteri Sumanto; Kartika Hajar Kirana; Kusnahadi Susanto (Jurnal Penelitian Pendidikan IPA, 2022)
The existence of trees is very beneficial for humans’ life. There are utilizations of tree such as urban planning and reforestation. However, the tree can be dangerous when the tree is aged and decay because of several factors that might be cause fallen tree. Furthermore, the monitoring activity is needed to know the condition of the tree. One of the methods that can be used to detect hollow in living tree is Electrical Resistivity Tomography (ERT). The ERT is an efficient and nondestructive method that can be potential to estimate resistivity cross section. The measurement of ERT conducted on Swietenia mahagoni and Gmelina with unhealthy and healthy condition visually. The data processed using Res2Dinv and reconstructed for obtaining 2D resistivity cross section. The results shows that the unhealthy Swietenia mahagoni has logarithmic resistivity value range between 0.1-1 Ωm and the healthy Swietenia mahagoni has 1-4 Ωm. Meanwhile, the unhealthy and healthy Gmelina has logarithmic resistivity value range between 0.5-4.5 Ωm and 0.5-3 Ωm, respectively. It is shows that the tree indicated health visually from biological view does not mean the tree is decay. It might be influenced by phenology factor and/or the species of the tree.